Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1007/s00125-008-1217-3
|View full text |Cite
|
Sign up to set email alerts
|

Are elevated circulating intercellular adhesion molecule 1 levels more strongly predictive of diabetes than vascular risk? Outcome of a prospective study in the elderly

Abstract: Aims/hypothesis The aim of this prospective study was to determine whether circulating intercellular adhesion molecule (ICAM) 1, as a potential surrogate of 'endothelial activation', is more strongly associated with risk of vascular events than with incident diabetes. MethodsWe related baseline ICAM-1 levels to vascular events (866 CHD and stroke events in 5,685 participants) and incident diabetes (292 in 4,945 without baseline diabetes) in the elderly over 3.2 years of follow-up. Results ICAM-1 levels correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…A large body of evidence points towards the involvement of subclinical, low-grade inflammation and increased systemic levels of acute phase proteins, cytokines and adhesion molecules in patients with T2D [4]. Previous studies show that sICAM-1 predicts diabetes [30], and sICAM-1 associates more strongly with diabetic risk than cardiovascular risk [31]. Furthermore, it has been shown that endothelial cells can secrete sST2 in response to treatment with various inflammatory mediators [32].…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence points towards the involvement of subclinical, low-grade inflammation and increased systemic levels of acute phase proteins, cytokines and adhesion molecules in patients with T2D [4]. Previous studies show that sICAM-1 predicts diabetes [30], and sICAM-1 associates more strongly with diabetic risk than cardiovascular risk [31]. Furthermore, it has been shown that endothelial cells can secrete sST2 in response to treatment with various inflammatory mediators [32].…”
Section: Discussionmentioning
confidence: 99%
“…All articles were published in English after 1994. We found 15 prospective population-based cohort studies, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] 3 prospective nested case-control studies, [31][32][33] and 5 prospective case-cohort studies. [34][35][36][37][38] The studies examined mainly white participants from Europe, the United States, and Australia.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Eleven studies 17,22,26,28,31,32,[34][35][36][37][38] investigated the association of microvascular dysfunction as measured by plasma markers of endothelial dysfunction and incident T2DM. Table I in the online-only Data Supplement shows a higher incidence of T2DM at higher levels of sE-selectin, sICAM-1, and vWF at baseline.…”
Section: Microvascular Dysfunction and Risk Of T2dmmentioning
confidence: 99%
See 2 more Smart Citations